Pengaruh Metode Brainstorming pada Model Learning Cycle 5E terhadap Hasil Belajar Peserta Didik Kelas VIII SMPN 2 Sukamaju Kab. Luwu Utara - Suciati Udin; Ramlawati Ramlawati; Sitti Rahma Yunus (Celebes Science Education, 2022)
This study aims to find out 1) the increase in learning outcomes of grade VIII students of SMPN 2 Sukamaju taught using brainstorming method on the learning cycle 5e model, 2) the increase in learning outcomes of grade VIII students of SMPN 2 Sukamaju taught using the learning cycle 5e model without brainstorming method, 3) whether there is influence of brainstorming method on learning cycle 5e model on learning outcomes of grade VIII students of SMPN 2 Sukamaju. The research was conducted using Nonequivalent Design Group Control. This research was conducted at SMPN 2 Sukamaju North Luwu 2018/2019. The sampling using purposive sampling technique . The study sample used 33 people in the experimental class and 32 people in the control class. The instruments used learning outcomes test sheets. Data analysis was performed using descriptive and inferential analysis. Analysis of increasing learning outcomes were using N-Gain, reveals that student’s learning outcomes scores were taught by brainstorming methods on the learning cycle 5e model is 0,66 in the medium category. While the learning outcome score for the control class that used the learning cycle 5e model without the brainstorming method is 0,54 in the medium category. Based on the results of hypothesis testing showed that Ha was accepted at α = 0,05, for the results of learning outcomes obtained tcount = 2,76 ˃ ttable = 1,67. It could be concluded that the brainstorming method in learning cycle 5e model has an effect on increasing learning outcomes of grade VIII students of SMPN 2 Sukamaju on the subject matter of additives and addictive.